Kesalahan Sintaksis pada Abstrak Berbahasa Inggris di Jurnal Ilmiah - Siska Bochari; Hastini; Afrillia Anggreni; Hasan Basri (Universitas Tadulako, 2022)
Students who write theses must make an article published in a scientific journal. The most difficult part for non-English students is writing abstract into English. The aims of this study was to find errors made by students in writing abstracts and to find the most dominant types of errors in writing abstracts. The research used descriptive qualitative method. The number of articles published throughout 2020 is 30. Researchers took 30% from the number of articles so the sample of this study is 9.The students' errors in writing abstract are: 1) not understanding the suitability of subject and verb, not changing verb forms to past forms, not understanding the use of connectors, 2) changing word order influenced by source language, 3) reducing suffix determining: word class, singular plural forms, and tenses, 4) removing prepositions and objects, 5) generalizing verb forms for both singular and plural subjects, including past and present forms, so the use of suffixes is not clear. The most dominant type of error made by students is misinformation which is the use of tense and auxiliary verb BE causing errors in subject verb agreement